The relation between dopamine D2 receptor blockade and the brain reward system: a longitudinal study of first-episode schizophrenia patients. Issue 2 (15th January 2020) - Wulff, Sanne; Nielsen, Mette Ødegaard; Rostrup, Egill; Svarer, Claus; Jensen, Lars Thorbjørn; Pinborg, Lars; Glenthøj, Birte Yding
Abstract: Background: Psychotic symptoms have been linked to salience abnormalities in the brain reward system, perhaps caused by a dysfunction of the dopamine neurotransmission in striatal regions. Blocking dopamine D2 receptors dampens psychotic symptoms and normalises reward disturbances, but a direct relationship between D2 receptor blockade, normalisation of reward processing and symptom improvement has not yet been demonstrated. The current study examined the association between blockade of D2 receptors in the caudate nucleus, alterations in reward processing and the psychopathology in a longitudinal study of antipsychotic-naïve first-episode schizophrenia patients. Methods: Twenty-two antipsychotic-naïve first-episode schizophrenia patients (10 males, mean age 23.3) and 23 healthy controls (12 males, mean age 23.5) were examined with single-photon emission computed tomography using 123 I-labelled iodobenzamide. Reward disturbances were measured with functional magnetic resonance imaging (fMRI) using a modified version of the monetary-incentive-delay task. Patients were assessed before and after 6 weeks of treatment with amisulpride. Results: In line with previous results, patients had a lower fMRI response at baseline (0.2 ± 0.5 v. 0.7 ± 0.6; p = 0.008), but not at follow-up (0.5 ± 0.6 v. 0.6 ± 0.7), and a change in the fMRI signal correlated with improvement in Positive and Negative Syndrome Scale positive symptoms ( ρ = −0.435, p = 0.049). In patients responding to treatment, a correlation between improvement in the fMRI signal and receptor occupancy was found ( ρ = 0.588; p = 0.035). Conclusion: The results indicate that salience abnormalities play a role in the reward system in schizophrenia. In patients responding to a treatment-induced blockade of dopamine D2 receptors, the psychotic symptoms may be ameliorated by normalising salience abnormalities in the reward system.